OMG oh my god - Kumar, Akshay 1967-; Rawal, Paresh 1950-; Cakrabartī, Miṭhuna 1947- (Viva Entertainment, 2012)
Atheist Kanjilal Mehta takes 'God' to court after an earthquake destroys his shop. Suddenly, 'Krishna Vasudev Yadav' shows up - does divine intervention occur?